How strong is the integrity disclosure in Indonesian Province website? - Hellenikapoulos, Maria; Utami, Intiyas (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2021)
The high level and trend of corruption in Indonesia Province could hinder the goal of Sustainable Development Goals point 16. This study aims to identify disclosures of integrity through websites and classify the Indonesia Provinces into 3 categories, namely high, medium, and low based on the integrity disclosure index using institutional theory. The data is based on content analysis to analyze practices through disclosure of integrity on 34 Indonesian Province websites using the Integrity Framework Disclosure Index instrument. The findings indicate that Indonesia has disclosed 775 items (48%). The items of vision, mission, and integrity report are the biggest disclosed items among other items that show Indonesia’s effort to create a “good image” in the public eyes. Several Provinces are in the moderate category because of a strategic issue in the field of education. Local governments still have to review the increase in integrity disclosure on websites and their real-life implementation to improve integrity and fight corruption in Indonesia.